A Case Study of Chronic Iliopsoas Tendinopathy and Sacroiliac Joint Dysfunction Masquerading As Pelvic Girdle Pain - Mank, Victoria M (Cureus, 2021)
Pain related to pregnancy can occur anytime between conception to the postpartum period. Pregnancy and the following months after birth are a time of physical change to the woman’s body, with significant hormonal effects. We present a case of a young female with chronic pain several years after her second pregnancy that presented a diagnostic challenge. She was initially diagnosed with persistent pelvic girdle pain (PGP) type 2, responded somewhat to appropriately targeted pelvic floor therapy, with a plateau in her progress. The diagnosis was revised to PGP type 4, with some improvement in pain with customized therapy. Her treatment again changed with a focus on sacroiliac joint (SIJ) dysfunction and iliopsoas tendinopathy with excellent and complete resolution of her pain. The overlapping nature of these diagnoses caused a significant challenge in creating a tailored physical therapy approach to her pain that eventually led to her final diagnosis being one of exclusion. Treatment was focused on optimization of joint mobility and tissue lengthening, with the resolution of her pain.